2xy-x+y=3 =>x(2y-1)+y=3 =>2x(2y-1)+2y=6 =>2x(2y-1)+2y-1=5
=>(2x+1)(2y-1)=5
Tự lập bảng nha
=>(x,y) thuộc (0,3);(2,1);(-1,-2);(-3,0)
2xy - x + y = 3
=> 2(2xy - x + y) = 6
=> 4xy - 2x + 2y = 6
=> 2x(2y - 1) + (2y - 1) = 5
=> (2x + 1)(2y - 1) = 5
=> 2x + 1; 2y - 1 \(\in\)Ư(5) = {1; -1; 5; -5}
Lập bảng :
2x + 1 | 1 | -1 | 5 | -5 |
2y - 1 | 5 | -5 | 1 | -1 |
x | 0 | -1 | 2 | -3 |
y | 3 | -2 | 1 | 0 |
Vậy ...
3xy + 2x - y = 2
=> 3(3xy + 2x - y) = 6
=> 9xy + 6x - 3y = 6
=> 3x(3y + 2) - (3y + 2) = 4
=> (3x - 1)(3y + 2) = 4
=> 3x - 1; 3y + 2 \(\in\)Ư(4) = {1; -1; 2; -2; 4; -4}
Lập bảng :
3x - 1 | 1 | -1 | 2 | -2 | 4 | -4 |
3y + 2 | 4 | -4 | 2 | -2 | 1 | -1 |
x | 2/3(ktm) | 0 | 1 | -1/3(ktm) | 5/3(ktm) | -1 |
y | 2/3(ktm) | -2 | 0 | -4/3(ktm) | -1/3(ktm) | -1 |
Vậy ...
3xy+2x-y=2 =>x(3y+2)-y=2 =>3x(3y+2)-3y=6 =>3x(3y+2)-3y-2=4
=>3x(3y+2)-(3y+2)=4 =>(3x-1)(3y+2)=4
tự lập bảng nữa nhé
=>(x,y) thuộc (1,0);(-1,-1);(0,-2)